Buddhism and South Asian Folklore - Lewis, Todd T. (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Background: This article examines interaction between Buddhism and South Asian folklore exploring the influences of Buddhist traditions over culture, traditions, beliefs and practices of the local people specifically in northern India since the origin of Buddhism in the region. Objective: The objective of the paper is to focus the impacts of the Buddhist principles in various culture, custom and folklore in the South Asian region as the Dhamma gets expanded across South Asia and beyond. Methodology: Interdisciplinary methodology is employed while going through the research work, drawing from historical, textual, ethnographic, and sociological approaches to analyze the relationships between Buddhism, folklore, and contemporary South Asian society. Result: The paper depicts how the states were formed adopting the values of the Dhamma and how it brought a cultural integration becoming a popular religious practice in the region. There were people who preferred monastic life with Spiritual Practices and Meditations under the guidance of core Buddhist Philosophy whereas there were others, the householders, who were much more influenced by Buddhist rituals and local folklore. The role of Buddhist Monks and Nuns in facilitating the laities with ritual practices and Buddhist teachings is highlighted in the article. The article reflects the role of monastic folklorists in transforming folk traditions into an important part of Buddhist Practices by mixing up local deities, spirits and rituals into Buddhist cosmology. Jatakas and Avadanas stories of the Buddha's past lives are highlighted in the paper as the key sources of Teaching Buddhist ethics and doctrines to the common people. Conclusion: The paper investigates how Buddhism, in South Asia, got flourished with its modest engagement with various cultures and traditions in the region with significant influences over the folklore of the contemporary societies